Applying the Simplex Method to Optimize Employee Distribution to Increase Sales Internet Data Package - Mulkan Azhari; Syahril Efendi; Purwanto Purwanto; Halim Maulana (UMSU, 2023)
The goal of this article is to ascertain how to maximize sales of internet data packages while keeping the company's marketing budget within reasonable bounds. The technique utilized is linear programming using the Simplex method; this approach's benefit is the ability to compute two or more choice variables, which produces results that are superior to those of the graphical method. Variable Three are utilized in this study: senior marketing (X1), junior marketing (X2), and apprentice marketing (X3). The maximum amount of data package cards that may be sold by the three marketing is 3000. The marketing senior target can sell 1200 packages, whereas the marketing junior target can sell 1200 packages, according to optimization simulation findings using the simplex approach.